Recurrent Acute Pericarditis Triggered by COVID-19 Disease - Waheed, Maham Akbar; Rojas-Marte, Geurys (Cardiology and Cardiovascular Medicine, 2021)
A 37-year-old woman presented with persistent chest pain and shortness of breath since four weeks prior to admission. Outpatient ECG was suggestive of acute pericarditis, however her symptoms persisted despite treatment with colchicine and NSAIDs. Serology revealed presence of COVID IgG antibodies. We discuss the case of late presenting, recurrent acute pericarditis in the context of COVID disease.